Rancang Bangun Aplikasi E-commerce Berbasis Web Menggunakan Metode Waterfall - Aisyah Isnaeni Ramadhanti; Isa Faqihuddin Hanif (Journal of Information System Research (JOSH), 2026)
Dunia Anak Store currently still applies conventional marketing systems and manual recording, which results in limited market reach and inaccuracies in stock data. This research aims to develop a web-based sales information system to address these issues using the waterfall method. The development stages include requirements analysis, system design, implementation, and testing. System testing was carried out in two phases: alpha testing to validate functionality, and beta testing involving direct users to measure system feasibility. The results of alpha testing showed that all features functioned correctly according to the design, while beta testing indicated that the system was well accepted by users. In conclusion, this system successfully improved transaction efficiency, expanded promotional reach, and resolved stock data accuracy problems at Dunia Anak Store.